Endonuclease G mediates α‐synuclein cytotoxicity during Parkinson's disease. (15th October 2013) - Büttner, Sabrina; Habernig, Lukas; Broeskamp, Filomena; Ruli, Doris; Vögtle, F Nora; Vlachos, Manolis; Macchi, Francesca; Küttner, Victoria; Carmona‐Gutierrez, Didac; Eisenberg, Tobias; Ring, Julia; Markaki, Maria; et al.
<x xml:space="preserve">Abstract</x> Malfunctioning of the protein α‐synuclein is critically involved in the demise of dopaminergic neurons relevant to Parkinson's disease. Nonetheless, the precise mechanisms explaining this pathogenic neuronal cell death remain elusive. Endonuclease G (EndoG) is a mitochondrially localized nuclease that triggers DNA degradation and cell death upon translocation from mitochondria to the nucleus. Here, we show that EndoG displays cytotoxic nuclear localization in dopaminergic neurons of human Parkinson‐diseased patients, while EndoG depletion largely reduces α‐synuclein‐induced cell death in human neuroblastoma cells. Xenogenic expression of human α‐synuclein in yeast cells triggers mitochondria‐nuclear translocation of EndoG and EndoG‐mediated DNA degradation through a mechanism that requires a functional kynurenine pathway and the permeability transition pore. In nematodes and flies, EndoG is essential for the α‐synuclein‐driven degeneration of dopaminergic neurons. Moreover, the locomotion and survival of α‐synuclein‐expressing flies is compromised, but reinstalled by parallel depletion of EndoG. In sum, we unravel a phylogenetically conserved pathway that involves EndoG as a critical downstream executor of α‐synuclein cytotoxicity.